Migraine headaches in a nutshell - Natalie Schellack; O Mogole; N Magongwa; F Makola (South African Family Practice)
This article aims to provide a concise, high-level overview of the classification, management and treatment of migraine. Migraine is a common, debilitating neurological disorder that is characterised by the presence of severe headaches, which may last anything from a few hours to a few days (4–72 hours). Thus, the condition is characterised by episodes of severe migraine headache, frequently accompanied by nausea and vomiting. These headaches may be unilateral or bilateral, and patients may also experience a range of associated features. Acute attacks require rapid, abortive treatment and the rate of recurrence needs to be reduced and managed using effective prophylactic measures.